Depolarization in Disagreements through high-quality listening - (:unkn) unknown (My University, 2026)
The world is more polarized than ever, and conversations occurring daily between acquaintances, co-workers, family members, decision-makers, politicians, and others drive the nature of these conversations and their impact on our polarized societies. These